Factores psicosociales que pretenden a desarrollar conductas disruptivas en adolescentes y jóvenes que realizan el servicio militar en el batallón de infantería motorizado N°2 Imbabura de la ciudad de Santa Rosa. - Paredes Vargas, Jonny Fernando (2015)
The development of this thesis: Psychosocial factors that seek to develop disruptive behavior in adolescents and young adults who perform military service in the infantry battalion motorized No. 2 Imbabura city of Santa Rosa , is a research -oriented describe the psychological and social factors that predispose the development of disruptive behavior in adolescents and young people who perform military service in the motorized infantry battalion No. 2 Imbabura city of Santa Rosa for which a methodological process based on inductive, deductive, hypothetical statistical methods , the same as those supported in the techniques of observation, interviews and survey was developed.